THE HEDGE EFFECTIVENESS FOR LIVE CATTLE MARKET IN RIO GRANDE DO SUL SQUARE - Guerra, Renata Rojas; Freitas, Claílton Ataídes de; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708813 Considering the importance performed by the cattle production in the Rio Grande do Sul state’s economy, the objective of this study is to identify whether the operations done with regards hedge in the future market of the BM&F provide effective results as a way to mitigate the risks arising from price fluctuations. The study aims to collaborate for the academic debate in the sense to test empirically a risk analysis tool. It also contributes for the farmers in the state, who may use this information as decision criteria to make financial strategies. In this regards, were gathered price time series of cattle for both Rio Grande do Sul and contracts negotiated in the future market traded in the BM&F. With this information and based on the Portfolio Theory, were performed a series of econometric tests in order to prove the efficiency of using hedge. The model Var type was estimated. The results show that both series are stationeries in first degree and are co-integrated. However, the results of the series are relatively low with regards the optimal ratio and effectiveness of hedge with about 5,61% and 12%, respectively. Besides, the optimal ratio it only significant at confidence superior levels at 26,8%. These findings suggest that this toll is not suitable to manage risks for cattle farmers in the state of Rio Grande do Sul. Therefore, factors as climatic conditions, the production cost, and the entrepreneurs’ profile, which vary according the analyzed region, may justify the incidence of low expressive results.